Index of fungi described from the Zingiberaceae - Bussaban B. (2014)
Fungi described from members of the Zingiberaceae are listed under the host genera. Within each host genus the fungi are grouped, and listed alphabetically under Oomycetes, Ascomycetes, Basidiomycetes, and anamorphic fungi. In total, 170 fungi have been described from 17 genera of Zingiberaceous plants, comprising 1 species of Oomycetes, 30 Basidiomycetes, 56 Ascomycetes, and 83 anamorphic fungi. Seven taxa have been described from Aframomum, 25 from Alpinia (host for 1 species also cited as Catymbrium), 22 from Amomum, 1 from Catymbrium (also on Alpinia), 30 from Costus, 18 from Curcuma, 10 from Elettaria, 1 from Geostachys, 3 from Globba, 9 from Hedychium, 1 from Hitchenia, 1 from Kaempferia, 1 from Nicolaia, 5 from Renealmia, 1 from Roscoea, 1 from Stahlianthus, 28 from Zingiber, and 7 from unknown Zingiberaceae. The fungi have been described from 34 countries, most commonly India (38 taxa), China (15 taxa), Brazil (13 taxa), Taiwan (13 taxa), Philippines (13 taxa), and Indonesia (10 taxa). The original reference, collection, and herbarium details known to us are given for each taxon.